Phatic formulas in teaching Spanish as a foreign language: from theory to practice - Anastasia Kutkova (Ибероамериканские тетради)
The presentation consists of two parts: the theoretical part presents the topic and proves the importance of studying phatic formulas from the communicative and methodological points of view; and the practical part contains sample assignments. It is a question of Spanish lexical units such as: vale, ¿vale?, ¿sabes?, ¿perdón?, ¡No me lo digas!, la verdad es que, mira, etc.